Two new species of sand-bubbler crabs, Scopimera, from North China and the Philippines (Crustacea: Decapoda: Dotillidae) - Wong, Kingsley J. H.; Shih, Hsi-Te; Chan, Benny K. K. (Zootaxa, 2011)
Two undescribed species of Scopimera are herein described. Scopimera sheni sp. nov. from Qingdao, represents the fourth species of the genus to be recognized from North China. Scopimera philippinensis sp. nov. is the first record of the genus from the Philippines. Morphologically both new species belong to the “normal form” Scopimera (sensu Kemp 1919). Amongst other characters, each can be distinguished by its diagnostic male first gonopod. Mitochondrial cytochrome oxidase I (COI) gene sequences showed two distinct clades. An East Asia group (Chinese coasts, Japan, Korea and Taiwan) consisting of S. globosa De Haan, 1835, S. ryukyuensis Wong, Chan et Shih, 2010, S. sheni sp. nov., S. longidactyla Shen, 1932 and S. curtelsona (= S. cutelsoma) Shen, 1936; and a Southeast Asia group consisting of the closely related S. philippinensis sp. nov. and S. intermedia Balss, 1934. A dichotomous key is provided for all “normal forms” of Scopimera species.